Dynamic Quality Tracking of Natural Gas and Hydrogen Mixture in a Portion of Natural Gas Grid. (August 2015) - Guandalini, Giulio; Colbertaldo, Paolo; Campanari, Stefano
Abstract: Direct injection of alternative fuels (biomethane, hydrogen) in the natural gas grid appears to be a promising solution to reach environmental objectives of CO2 emission reduction in the current energy scenario. This approach is justified by the large amount of biogas producible, which can be upgraded to biomethane; while another proposed solution to increase renewable energy sources exploitation lies in producing hydrogen from excess wind energy, followed by injection in the natural gas grid. Nevertheless, compliance with composition limitsand quality constraints in the resulting natural gas mixture has to be analysed in both stationary and dynamic operations, tracking the gas quality downstream the injection point of the alternative fuels. A model was developed to simulate unsteady operation of a portion of gas grid dealing with realistic industrial and residential consumptions concentrated in offtake points. Two case studies were investigated focusing on the comparison between different amounts of hydrogen injectionin the pure natural gasflow, yieldingcomposition, flow rate and pressure profiles. The analysis shows how imposed quality thresholds can berespected, although the hydrogen fraction within the natural gas mixture is highly sensitive to the profile and size of the loads connected to the gas pipeline.